RETRACTED: Ghrelin Alleviates Intestinal Dysfunction in Sepsis Through the KLF4/MMP2 Regulatory Axis by Activating SIRT1 - Li, Bin; Dou, Zhimin; Zhang, Lei; Zhu, Lei; Cao, Yongqiang; Yu, Qin (Frontiers in Immunology, 2021)
Intestinal barrier dysfunction is an important contributor to morbidity caused by sepsis. This study investigates the molecular mechanism by which Ghrelin affects intestinal dysfunction in rat model of sepsis. A rat model of sepsis was established by cecal ligation and puncture (CLP), revealing that Ghrelin was downregulated when sepsis occurs. Increases in the levels of inflammatory factors tumor necrosis factor α (TNF-α), interleukin-1 (IL-1β), IL-6, gastrin, γ-H2AX and 8-OHdG was also detected in this model system, as was an overall increase in oxidative stress. Introduction of exogenous Ghrelin inhibited these increases in inflammatory response and oxidative stress, leading to a reduction of overall sepsis-induced intestinal dysfunction. Ghrelin was then shown to activate SIRT1 expression in vitro, while SIRT1 was found to co-express with KLF4, which in turn was predicted to bind to matrix metalloproteinase 2 (MMP2) promoter. Finally, gain- and loss-of-function experiment demonstrated that SIRT1 upregulated the expression of KLF4 to downregulate MMP2. Collectively, Ghrelin inhibits the oxidative stress and intestinal dysfunction to attenuate sepsis by activating SIRT1 and regulating a KLF4/MMP2 regulatory axis.